Effective Construction of Hyperbranched Multicyclic Polymer by Combination of ATRP, UV-Induced Cyclization, and Self-Accelerating Click Reaction - Liu, Chao; Fei, Yi-yang; Zhang, Hua-long; Pan, Cai-yuan; Hong, Chun-yan (Macromolecules, 2019)
Multicyclic polystyrene (PS) with hyperbranched structure was constructed in an efficient way. First, a seesaw-type PS was synthesized via atom transfer radical polymerization (ATRP) using a Y-shaped ATRP initiator containing one hydroxyl at center and bromine at each end. After azidation, the anthryl and hydroxyl groups were introduced to the ends of the polymer chain by click reaction with a trifunctional molecule bearing alkynyl, hydroxyl, and anthryl groups (alkynyl-OH-ant). By irradiation with 365 nm UV light in a highly dilute condition, cyclic polymer with three hydroxyl groups (c-PS-(OH)3) can be obtained; then it was converted to a cyclic polymer containing three azides (c-PS-(N3)3) by bromination of the hydroxyl groups and azidation. This “A3” cyclic macromonomer was then used to construct hyperbranched multicyclic polymers via self-accelerating click reaction with sym-dibenzo-1,5-cyclooctadiene-3,7-diyne (DBA). The properties of obtained polymer were characterized by NMR, FT-IR, MALDI-TOF MS, and TD-SEC. It was calculated from the MALLS results that there were about 35 “small rings” in the multicyclic polymer. Moreover, because of the photocleavage reaction of the anthracene dimer, this hyperbranched multicyclic polymer can be cleaved to long-chain hyperbranched PS by irradiation with 254 nm UV light.